Draft Annual Plan 1975-76 (Part-II) Government of Assam - Planning Commission (Planning Commission, 1975)
The deficiency and shortages in the road system in Assam are very high compared to the rest of the country. Assam's read complex is very vital for the entire North-Eastern region as communication between the outlying States like Manipur, Nagaland, Tripura, Meghalaya and Union Territories like Mizoram and Arunachal Pradesh and the rest of the country have to loss through Assam. But the deficiencies and shortages in the road system of the State cannot be removed during the Fifth Five Year plan itself due to various constraints.
Government of Assam, Planning and Development Department